Potential Manipulations to Restore Aberrant Myelopoiesis: The Role of New Colony-Stimulating Factors and other Agents - James J Rusthoven (Canadian Journal of Infectious Diseases)
A rapidly growing number of new recombinant human colony-stimulating factors (CSFs) are entering various phases of clinical testing. With the recent approval of granulocyte colony-stimulating factor (G-CSF) and granulocytemacrophage colony-stimulating factor (GM-CSF) for clinical use, newer CSFs will be developed for a widening spectrum of disease states singularly and in combination with other CSFs. Interleukin (IL)-3 is being tested in early clinical trials, and combination studies with G-CSF and GM-CSF are to follow soon. lL-6 presently is in animal model testing, but already shows promise of amplifying the restorative capabilities of IL-3. IL-4 , GM-CSF and others. As a single agent, IL-6 may be instrumental in clarifying disease processes and therapeutics in diseases ranging from multiple myeloma to glomerulonephritis. Agents such as WR-2721 which appear to protect early progenitors with or without proliferative effects likely will add another dimension to the therapeutic alternatives for restoring aberrant myelopoiesis. The range of potential clinical application for new CSFs rapidly is expanding beyond oncology to include diseases where infection prevention or therapy against established infection is the prime target of treatment.